2022
DOI: 10.1093/cercor/bhac429
|View full text |Cite
|
Sign up to set email alerts
|

Right dorsolateral prefrontal cortex regulates default prosociality preference

Abstract: The dorsolateral prefrontal cortex has been shown to be associated with prosocial behavior. However, the direction of this relationship remains controversial. To resolve inconsistencies in the existing literature, we introduced the concept of default prosociality preference and hypothesized that this preference moderates the relationship between gray matter volume in the dorsolateral prefrontal cortex and prosocial behavior. This study analyzed the data of 168 participants obtained from voxel-based morphometry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…However, in different contexts that require more strategizing (e.g., interdependent economic games), the LPFC’s has been positively correlated with selfish decision making 42 . Especially individuals who are by nature inclined towards altruism might need to restrain their prosocial intuition and rely on increased LPFC input to become more calculative and protect themselves from free-riders 43 , 44 . The modulatory role of context and individual differences on reward-based decision-making is not new 45 ; the extent to which alignment decisions are similarly affected, however, still requires a more holistic study of how different neural systems that feed into the VS are interconnected, which should go hand in hand with more fine-grained fMRI analyses (i.e., connectivity and pattern analysis).…”
Section: Discussionmentioning
confidence: 99%
“…However, in different contexts that require more strategizing (e.g., interdependent economic games), the LPFC’s has been positively correlated with selfish decision making 42 . Especially individuals who are by nature inclined towards altruism might need to restrain their prosocial intuition and rely on increased LPFC input to become more calculative and protect themselves from free-riders 43 , 44 . The modulatory role of context and individual differences on reward-based decision-making is not new 45 ; the extent to which alignment decisions are similarly affected, however, still requires a more holistic study of how different neural systems that feed into the VS are interconnected, which should go hand in hand with more fine-grained fMRI analyses (i.e., connectivity and pattern analysis).…”
Section: Discussionmentioning
confidence: 99%
“…60 For example, previous studies have demonstrated that greater DLPFC thickness and longer decision-making times are associated with decreased prosocial behaviour 61 and this trend is stronger in highly prosocial individuals. 30,31 A possible explanation for this association is the risk of exploitation by others through cognitive control. 30 In human society, engagement in prosocial behaviour can cause exploitation; therefore, intuitive engagement in prosocial behaviour in risky situations can be dangerous.…”
Section: Discussionmentioning
confidence: 99%
“…28 Humans demonstrate adaptable prosocial decision-making in response to social norms, including fairness norms and other social factors, by controlling for and overriding intuitive and/or preferential choices. [29][30][31][32][33] Cognitive control is believed to be crucial for facilitation of flexible behavioural adaptations. [18][19][20] Cognitive control and the DLPFC play prominent roles in complying with social norms, including those related to fairness.…”
mentioning
confidence: 99%
“…To illustrate, activity in brain areas involved in cognitive control has been found to be linked to honesty in dishonest individuals and cheating in honest individuals (Speer et al, 2020). Similarly, a recent study has shown that larger dlPFC volume is associated with more prosociality in selfish, and with less prosociality in prosocial individuals (Tanaka et al, 2023). In addition, research has provided evidence that prosocial individuals show shorter reaction times when making prosocial choices, and selfish individuals when making selfish ones (Hutcherson et al, 2015;Krajbich et al, 2015;Yamagishi et al, 2017), suggesting that higher conflict in Predicted probabilities for stimulation conditions and decision-conflict.…”
Section: Discussionmentioning
confidence: 97%
“…In our view, however, our results do not imply that lower levels of self-control capacity generally lead to more environmentally sustainable behavior. In fact, research on prosocial and honest decision-making has shown that whether self-control increases or decreases prosociality or honesty depends on an individuals' default preference, which is shaped by personality and context (Gross et al, 2018;Hackel et al, 2020;Speer et al, 2020;Tanaka et al, 2023). To illustrate, activity in brain areas involved in cognitive control has been found to be linked to honesty in dishonest individuals and cheating in honest individuals (Speer et al, 2020).…”
Section: Discussionmentioning
confidence: 99%